2011
DOI: 10.1186/1746-6148-7-54
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of combination of Mini-and Microsatellite loci to sub-type Mycobacterium avium subsp. paratuberculosis Italian type C isolates

Abstract: BackgroundMycobacterium avium subsp. paratuberculosis (Map) is the etiological agent of paratuberculosis. The aim of our study was to combine Mini-and Microsatellite loci analysis in order to explore the effectiveness of this sub-typing method in a group of Map isolates. For this purpose, 84 Italian Type C Map isolates, each from a different cattle herd, were submitted to MIRU-Variable-Number Tandem-Repeats (VNTRs) typing and Short Sequence repeats (SSRs) sequencing. Moreover, the method was used to analyse th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…The genotyping analysis revealed an unknown locus profile not previously found in Italy and an already described locus profile, which is largely diffused in Northern Italy (Ricchi et al, 2011).…”
Section: Mean Theoretical Input Of Map Cells By F57 Qpcr a Cultural Imentioning
confidence: 54%
See 2 more Smart Citations
“…The genotyping analysis revealed an unknown locus profile not previously found in Italy and an already described locus profile, which is largely diffused in Northern Italy (Ricchi et al, 2011).…”
Section: Mean Theoretical Input Of Map Cells By F57 Qpcr a Cultural Imentioning
confidence: 54%
“…For the allelic profile, the loci analysed were, respectively, MIRU 1, MIRU 2, MIRU 3, VNTR 25, VNTR 32, VNTR3, VNTR 7, VNTR 47, MLVA 1067 and MLVA 3527 for Mini satellites loci and SSR 1, SRR 2 and SSR 8 for Micro satellites. One sample (sample 51) showed a profile already described (3 7 5 3 8 2 2 3 2 2 7 >11 4) (Ricchi et al, 2011), denominated as MSV27 in the original publication. This allelic profile was found to be widespread in the Northern Italian herds.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…This might be due to random dispersal of the bacteria following large-scale processes such as cattle movements between herds. It has been reported that herds with an elevated turnover of cows show multiple genotypes (25,61), underscoring the importance of live animal trade in the transmission of M. avium subsp. paratuberculosis between herds.…”
Section: Figmentioning
confidence: 99%
“…paratuberculosis is a highly monomorphic species, and using a combination of multilocus typing methods is necessary to increase their overall discriminatory power, as previously shown for the M. tuberculosis complex (21,22) and M. avium subsp. paratuberculosis strains from different host species and different geographic locations (17,(23)(24)(25)(26). A typing scheme based on 8 MIRU-VNTR loci (called INMV typing) has been previously proposed for the M. avium complex (26).…”
mentioning
confidence: 99%